2016
DOI: 10.1021/acs.chemmater.6b01968
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Epitaxial Growth Kinetics in Functional Oxide Thin Films Grown by Pulsed Laser Annealing of Chemical Solutions

Abstract: The crystallization process and physical properties of different functional oxide thin films (Ce 0.9 Zr 0.1 O 2-y , LaNiO 3 , Ba 0.8 Sr 0.2 TiO 3 and La 0.7 Sr 0.3 MnO 3) on single crystal substrates (Y 2 O 3 :ZrO 2 , LaAlO 3 and SrTiO 3) are studied by pulsed laser annealing (PLA). A Nd:YAG laser source (λ=266 nm, 10 Hz and τ~3 ns) is employed to crystallize chemical solution deposited (CSD) amorphous/nanocrystalline films in atmospheric conditions. We provide new insight on the influence of photochemical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 94 publications
0
33
0
Order By: Relevance
“…This finding was attributed to the development of large temperature gradients and fast diffusion rates during laser processing. In addition, the rapid heating rates of laser irradiation are likely to prevent excessive coarsening of random orientations, contributing to a fast epitaxial growth . Microstructural analysis of the BST/LNO/LAO sample indicated that the BST film was completely epitaxial.…”
Section: Laser Irradiation Of Metal Oxides and Their Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding was attributed to the development of large temperature gradients and fast diffusion rates during laser processing. In addition, the rapid heating rates of laser irradiation are likely to prevent excessive coarsening of random orientations, contributing to a fast epitaxial growth . Microstructural analysis of the BST/LNO/LAO sample indicated that the BST film was completely epitaxial.…”
Section: Laser Irradiation Of Metal Oxides and Their Applicationsmentioning
confidence: 99%
“…Conventionally, the thermal treatment of MO films and nanostructures is conducted in an oven or a furnace in the temperature range of 300–1000 °C, depending on the material system, thermodynamics, and the intended effect . This process is associated with such issues as high thermal budget (thermal power), long processing times, and high degree of energy loss because sample dimensions are considerably smaller than the heated volume, and almost all of the energy is used to raise and lower the temperature of the substrate and the furnace itself.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical solution deposition (CSD) has appeared among the different processing techniques as an adaptable, low-cost and very powerful ex-situ approach for the bottom-up fabrication of functional oxide architectures with good stoichiometric control. For instance, it has been employed to successfully fabricate a broad range of oxides such as Pb(Zr,Ti)O3, (Ba,Sr)TiO3, LaNiO3, Ce1-xGdxO2-y (CGO), (La,Sr)MnO3, BiFeO3 and YBa2Cu3O7-x (YBCO) either as polycrystalline and epitaxial films, or in the form of interfacial nanostructures 10,35,38,[48][49][50][51][52][53][54][55] . Some attempts have been made to evaluate nucleation and coarsening in closed systems.…”
Section: Introductionmentioning
confidence: 99%